Hubungan Produktivitas Usahatani Padi dengan Kesejahteraan Rumah Tangga Petani Padi di Kecamatan Singaran Pati Kota Bengkulu: kesejahteraan; petani padi; produktivitas - Annisa Putri, Maharani; Yuliarso, M Zulkarnain; Ifebri, Rihan (innofarm, 2025)
The purpose of this research is to analyze the productivity of rice farming and the welfare of rice farming households in Singaran Pati Sub-District, Bengkulu City and the correlation between the two. The research location was selected purposively with the consideration that Singaran Pati Sub-District is one of the rice suppliers in Bengkulu City. The respondents consisted of 75 rice farmers who were selected using the simple random sampling method. The welfare of rice farming households was analyzed using indicators from BKKBN. The correlation between the productivity of rice farming and the welfare of rice farmer households was analyzed using the chi-square method. The results showed that the average productivity of rice farming in the research location was 4,8 tons/Ha. The level of households welfare of rice farmers in the research location with the highest percentage is KS II, which is 38,67%. The results showed a greater value of chi-square calculated than the value of the chi-square table so it was concluded that there is a correlation between the productivity of rice farming with the welfare of rice farmer households.